2014
DOI: 10.1097/ana.0000000000000028
|View full text |Cite
|
Sign up to set email alerts
|

Factors That Correlate With the Decision to Delay Extubation After Multilevel Prone Spine Surgery

Abstract: Background Multi-level spinal decompressions and fusions often require long anesthetic and operative times which may result in airway edema and prolonged post-operative intubation. Delayed extubation can lead to broncho-pulmonary infections and other complications. This study analyzed which factors correlated with the decision to delay extubation after multilevel spine surgery. Methods We reviewed the records of 289 patients having multilevel spine surgery lasting 8 hours or more in the prone position from 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(30 citation statements)
references
References 21 publications
4
25
0
1
Order By: Relevance
“…The significant surgery-related risk factors in our study include operative time and length of hospital stay, which is consistent with the literature. The mean operative time of our cases was 5.86 hours, which is within the range reported in the literature (5.7-10.85 hours) (26,28). Unlike Martin et al's study of wound infections in a pediatric population, we found that extension to the pelvis was not a risk factor in our sample (19)…”
Section: Surgery-related Risk Factorssupporting
confidence: 72%
“…The significant surgery-related risk factors in our study include operative time and length of hospital stay, which is consistent with the literature. The mean operative time of our cases was 5.86 hours, which is within the range reported in the literature (5.7-10.85 hours) (26,28). Unlike Martin et al's study of wound infections in a pediatric population, we found that extension to the pelvis was not a risk factor in our sample (19)…”
Section: Surgery-related Risk Factorssupporting
confidence: 72%
“…The prone position is typically utilized for spine surgeries requiring a posterior approach to the spinal column. Despite its convenience in terms of ease of access, the prone position carries with it significant and well-documented risks that can result in permanent disability (6)(7)(8). Coupled with the trend towards value based healthcare, considerations of alternative forms of surgical techniques that decrease operative times without compromising patient safety and surgical outcomes deserve investigation (9,10).…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have suggested that a prolonged operative time was associated with increased incidence of delay extubation and pneumonia after multilevel prone spine surgery [ 19 ]. Similarly, our study demonstrated a higher incidence of postoperative pulmonary complications among patients with CS undergoing operation lasting > 430 min.…”
Section: Discussionmentioning
confidence: 99%